2014
DOI: 10.1177/2040620714561579
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma: observation to transplantation

Abstract: Abstract:Mantle cell lymphoma as a rare non-Hodgkin B-cell lymphoma can present in different clinical presentations such as an aggressive form or a more indolent picture. Treatment modality is based on multiple factors including age, presence or absence of symptoms, and comorbidities. Watchful waiting is a reasonable approach for asymptomatic patients especially in elderly. In symptomatic patients, treatment is chemo-immunotherapy followed by maintenance immunotherapy or autologous bone marrow transplant. Allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 84 publications
(114 reference statements)
0
13
0
Order By: Relevance
“…While R-CHOP is commonly used in certain clinical situations, its use as initial treatment without subsequent consolidation with ASCT or maintenance rituximab has lost favor [Rajabi and Sweetenham, 2015]. A retrospective review conducted by LaCasce and colleagues showed R-CHOP resulted in inferior outcomes than the more intense R-HyperCVAD (rituximab, cyclophosphamide, vincristine, doxorubicin, and dexamethasone alternating with methotrexate and cytarabine) regimen, regardless of the use of consolidation with ASCT.…”
Section: Treatment Approaches To MCLmentioning
confidence: 99%
“…While R-CHOP is commonly used in certain clinical situations, its use as initial treatment without subsequent consolidation with ASCT or maintenance rituximab has lost favor [Rajabi and Sweetenham, 2015]. A retrospective review conducted by LaCasce and colleagues showed R-CHOP resulted in inferior outcomes than the more intense R-HyperCVAD (rituximab, cyclophosphamide, vincristine, doxorubicin, and dexamethasone alternating with methotrexate and cytarabine) regimen, regardless of the use of consolidation with ASCT.…”
Section: Treatment Approaches To MCLmentioning
confidence: 99%
“…At present, various treatments are used for MCL: Chemotherapy; bone marrow transplantation; radiotherapy; immunotherapy; and targeted therapy. However, to date, no consensus regarding the optimal treatment has been reached among physicians, and rapid relapses hamper their curative effect (19). As a result, MCL has a relatively short median survival time of 5–7 years (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mantle cell lymphoma (MCL) is an aggressive subtype of NHL and is generally considered incurable, even despite intensive therapeutic approaches. 23 It is characterized by the t(11:14) chromosomal translocation which results in dysregulation and overexpression of the cell cycle protein cyclin D1. 24 MCL accounts for~5-10% of NHL cases and has been increasing in incidence in the past two decades.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%